Analysis of hysteretic response of glass infilled wooden frames - Antolinc, David; Rajčić, Vlatka; Žarnić, Roko (Journal of Civil Engineering and Management, 2014)
The idea of the present study is to determine the performance of timber-glass hybrid shear wall exposed to monotone and cyclic horizontal in-plane load at the level of story height which is simulation of situation during earthquake or wind load. Fourteen quasi-static in-plane racking tests of shear wall specimens have been conducted where the specimens are composed of laminated timber frame and heat strengthened laminated glass panels, which are adhesive less, connected to wooden frame with friction only. For the evaluation of the experimental results the software (HYSPA+) was developed which is giving the information on normalised stiffness degradation and equivalent viscous damping coefficient based on the in-plane hysteresis response. The results are showing that described structural components are ductile with relatively high potential for dissipating of induced energy due to friction connection of glass panel and wooden frame. Observed damages were concentrated in timber frame joints, while glass panels remained entirely undamaged. In continuation of development of glass infilled wooden frames the configuration of frame joints will be modified to achieve its higher load bearing capacity and lower deformability.